Thoracic CT Scan Image in Transudate and Exudate Pleural Effusion Cases at Haji Adam Malik General Hospital Medan in January - September 2024 - Lokman, Yovita Belva; Putra, Dedy Dwi; Tarigan, Setia Putra; Malisie, Ririe Fachrina (Journal of Society Medicine, 2024)
Introduction: Pleural effusion is the most common pleural disease, typically diagnosed through thoracentesis. However, thoracentesis carries risks of complications. Chest CT scans offer a non-invasive alternative to assess pleural effusion and distinguish between exudate and transudate types. Methods: This retrospective cross-sectional study was conducted on patients with pleural effusion at Haji Adam Malik General Hospital, Medan. A total of 80 patients were included. Statistical analysis was performed to evaluate the correlation between demographic, clinical, and thoracic CT findings with the type of pleural effusion. The Mann-Whitney test determined the efficacy of attenuation values in differentiating exudate and transudate. Results: Of the 80 patients, 57 (71.3%) had exudative pleural effusion and 23 (28.7%) transudative. The sample comprised 43 males (53.8%) and 37 females (46.3%), with a mean age of 48.44 ± 18.532 years (range: 2–84 years). Significant correlations were found between the etiology of pleural effusion and pleural nodules with effusion type (p = 0.000 and p = 0.023, respectively). No significant correlations were observed between age, gender, or other CT findings with effusion type (p > 0.05). Attenuation values on CT scans effectively distinguished exudative from transudative effusion (p = 0.000). A cutoff attenuation value of 17.5 Hounsfield Units (HU) demonstrated an AUC of 0.887, with 84.2% sensitivity and 82.6% specificity. Conclusions: Thoracic CT scans are effective for differentiating exudative and transudative pleural effusion. Significant differences were identified in etiology, pleural nodules, and attenuation values, supporting the use of CT imaging as a non-invasive diagnostic method